Diagnostics of materials while processing metals under pressure - Nakhaichuk, O. V.; Ohorodnikov, V. A.; Muzychuk, V. I.; Derevenko, I. A. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The approaches to conducting diagnostics of material mechanical properties and the methodology of determining parameters of their technological certificate based on the phenomenological theory of deformation are presented. The definition of the given characteristics permits selecting materials for processes of the cold plastic deformation without labor-consuming experiments. It is also possible to forecast the technological heredity of half-finished products at different stages of their development.